2022
DOI: 10.1021/acsomega.2c03685
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Chitosan and Metal Oxide Additives on Improving the Organic and Biofouling Resistance of Polyethersulfone Ultrafiltration Membranes

Abstract: The combination of chitosan and metal oxides was utilized as an addition to improve the fouling resistance of polyethersulfone (PES) ultrafiltration membranes. Pure water flux, membrane hydrophilicity by the contact angle, scanning electron micrographs, and Fourier-transform infrared spectra were used to characterize the membranes. With the addition of metal oxides, the modified membrane’s water flux increased. The PES membrane with 0.25% wt chitosan and 2.0% wt AgNO3 had the highest flux and antibacterial act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…For example, carbon-based nanomaterials such as carbon nanotubes [ 17 , 18 ], graphene oxide [ 19 , 20 ], and carbon quantum dots [ 21 , 22 ] have been widely used to improve the permeance and antifouling properties of membranes. Metal [ 23 , 24 ] and metal oxide [ 25 , 26 ] blended PES membranes also exhibited improved filtration performance and antimicrobial properties. In addition, it was recently found that porous nanomaterials such as zeolite [ 27 , 28 ], metal–organic frameworks [ 29 , 30 ], and mesoporous carbon [ 31 ] increase the filtration performance of PES membranes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, carbon-based nanomaterials such as carbon nanotubes [ 17 , 18 ], graphene oxide [ 19 , 20 ], and carbon quantum dots [ 21 , 22 ] have been widely used to improve the permeance and antifouling properties of membranes. Metal [ 23 , 24 ] and metal oxide [ 25 , 26 ] blended PES membranes also exhibited improved filtration performance and antimicrobial properties. In addition, it was recently found that porous nanomaterials such as zeolite [ 27 , 28 ], metal–organic frameworks [ 29 , 30 ], and mesoporous carbon [ 31 ] increase the filtration performance of PES membranes.…”
Section: Introductionmentioning
confidence: 99%